Effect of chia (Salvia hispanica L.) seed mucilage powder on some physicochemical and rheological properties of ayran drinks - Elif Buse Tas; Feyza Dundar; Gizem Ozgur; Yusuf Yilmaz; Oguz Gursoy (Mljekarstvo)
In this study, chia seed mucilage powder (MP) was added into ayran drinks at different ratios (0.05, 0.10 and 0.15%, w/v), and its effect on physicochemical, rheological, microbiological and sensory properties of ayran drinks was determined during 10 days of storage at 4±1 °C. MP addition did not influence their major chemical composition significantly (p>0.05). Increasing MP ratio in drinks decreased the colour L* values of drinks while increasing their colour a* and b* values. Addition of 0.05, 0.10 and 0.15% MP reduced serum separation values of drinks by 25, 67 and 83%, respectively. The apparent viscosity value of control samples was 103.20 cP and increased to 134.25, 185.35 and 223.38 cP in ayran drinks with 0.05, 0.10 and 0.15% MP, respectively. The obtained results indicated that chia seed MP up to 0.05% can be used in ayran drink production to reduce serum separation and improve viscosity without any adverse effect on sensory liking scores.